Pengaruh Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian Kopi Jago Di Wilayah Johar Baru Jakarta Pusat - Zainab Ramadhina; Ai Netty Sumidartiny (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aims to analyze the influence of brand image and product quality on consumer purchasingdecisions at Kopi Kenangan Jago in the Johar Baru area, Central Jakarta. The method used isdescriptive quantitative by distributing questionnaires to 100 respondents. The data were analyzed usingvalidity and reliability tests, multiple linear regression, and hypothesis testing via SPSS 26. The resultsof the study show that brand image and product quality have a positive and significant influence, bothpartially and simultaneously, on purchasing decisions. Consumers consider brand image and productquality such as reliability, features, and durability when making purchasing decisions. Companies areadvised to maintain a balance between brand image and product quality in order to attract and maintainconsumer purchasing interest amidst market competition.Keywords: Brand Image, Product Quality, Purchasing Decisions, Jago Coffee, Johar Baru